PLZF Controls the Expression of a Limited Number of Genes Essential for NKT Cell Function - Gleimer, Michael; Von Boehmer, Harald; Kreslavsky, Taras (Frontiers in Immunology, 2012)
Natural killer (NKT) T cells exhibit tissue distribution, surface phenotype, and functional responses that are strikingly different from those of conventional T cells. The transcription factor PLZF is responsible for most of these properties, as its ectopic expression in conventional T cells is sufficient to confer to them an NKT-like phenotype. The molecular program downstream of PLZF, however, is largely unexplored. Here we report that PLZF regulates the expression of a surprisingly small set of genes, many with known immune functions. This includes several established components of the NKT cell developmental program. Expression of the transcriptional regulators Id2, previously shown to be required for iNKT cell survival in the liver and c-Maf, which shapes the NKT cytokine profile, was compromised in PLZF-deficient cells. Ectopic expression of c-Maf complemented the cells’ defect in producing IL-4 and IL-10. PLZF also induced a program of cell surface receptors which shape the NKT cell’s response to external stimuli, including the costimulatory receptor ICOS and the cytokine receptors IL12rb1 and IL18r1. As an ensemble, the known functions of the molecules whose expression is affected by PLZF explain many defects observed in PLZF-/- NKT cells.